INTEGRASI NILAI-NILAI PAI KE MATA PELAJARAN FISIKA UNTUK MENUMBUHKAN DOMAIN AFEKTIF SISWA - Ali Fatoni (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2018)
The integration of science is discussed today. The figures in this issue appear in the world. Mentioned among them Naquib al-Attas,and in Indonesia who keen to speak scientific integration is Amin Abdullah.This speech led to the birth of the 2013Curriculum in Indonesia with the demands of all subjects must contain a spiritual attitude (KI-1). This creates difficulties for teachers. Training and education program for teacher in applying The 2013 Curriculum is not technically in touch with their difficulties.Training and education program for teachermostly touchonly on aspects of teaching skills. This research is present to fill the gap that has not been filled by thattraining and education program. The results of this study is a simple description of the process of developing a physics textbook that begins from the study of old books and relevant theories for thisnew developmenttextbook to compiled new physics textbookincluding the content of Islamic values.